2005
DOI: 10.1002/ajh.20404
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of drug‐metabolizing enzymes and risk of childhood acute lymphoblastic leukemia

Abstract: The involvement of phase I and II enzymes is well documented in the metabolism of a wide range of drugs and xenobiotics. Single-nucleotide polymorphisms (SNPs) of these enzymes are also known to alter their protein expression and function. Moreover, genetic susceptibility and environmental exposure have been proposed to be an etiology of cancer. We hypothesized that polymorphisms of these enzymes might affect the risk of childhood acute lymphoblastic leukemia (ALL). CYP 1A1, CYP 3A4*1B, CYP 3A5*3, CYP 3A5*6, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 18 publications
8
31
0
Order By: Relevance
“…[17] In contrast, Pakakasama et al did not detect significant differences of genotype or allele frequencies for CYP3A5 * 3 polymorphism between ALL and control groups. [21] In the current meta-analysis, we examined the possible association between CYP3A5 * 3 polymorphism and ALL risk in children. The results we obtained were that the pooled ORs with 95% CIs of CYP3A5 * 3 heterozygous mutant, homozygous mutant, and (heterozygous + homozygous) mutant were 1.47 (0.97-2.21), 1.05 (0.62-1.79), and 1.67 (1.14-2.44) with p = 0.07, 0.86, and 0.009, respectively, indicating that there was significant association between CYP3A5 * 3 (heterozygous + homozygous) mutant and the risk of ALL in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] In contrast, Pakakasama et al did not detect significant differences of genotype or allele frequencies for CYP3A5 * 3 polymorphism between ALL and control groups. [21] In the current meta-analysis, we examined the possible association between CYP3A5 * 3 polymorphism and ALL risk in children. The results we obtained were that the pooled ORs with 95% CIs of CYP3A5 * 3 heterozygous mutant, homozygous mutant, and (heterozygous + homozygous) mutant were 1.47 (0.97-2.21), 1.05 (0.62-1.79), and 1.67 (1.14-2.44) with p = 0.07, 0.86, and 0.009, respectively, indicating that there was significant association between CYP3A5 * 3 (heterozygous + homozygous) mutant and the risk of ALL in children.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, five case-control studies including 1070 cases and 1125 controls met the inclusion criteria and were suitable for the meta-analysis. [17][18][19][20][21] A flow chart of the literature search and study selection is presented in Figure 1. The countries in which these studies had been carried out include Denmark, Thailand, China, and Brazil.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Published data indicate that xenobiotic-metabolizing polymorphic alleles in some populations correlate with increased risk of different lymphoproliferative diseases [18][19][20][21][22]. The majority of articles were devoted to the analysis of acute leukemia and, particularly, childhood leukemia [21,[23][24][25]. Thus, it would be interesting to investigate associations between polymorphous variants of xenobiotic-metabolizing genes and risk of development of other lymphoproliferative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown risk alterations owing to polymorphisms in genes encoding various metabolic enzymes. [9][10][11][12] In several investigations, variant alleles of the methylene-tetrahydrofolate reductase (MTHFR) gene have been associated with altered risk of acute leukemia whereas in some studies such effects were not observed. [13][14][15] The effects of polymorphisms in other folate metabolic pathway genes on susceptibility to childhood leukemia have also been investigated.…”
Section: Introductionmentioning
confidence: 99%